Ultra-refino de grão através de deformação plástica severa por ensaios de torção: simulação do processo ARB - Welbert Ribeiro Calado (2012)
The initial objective of this thesis was simulate the production of ultra-fine grained metals by means of severe plastic deformation processes, specifically the Accumulative Roll-Bonding process (ARB). This simulation was performed by means of warm torsion tests, using the typical parameters of the ARB process. Were studied twoplain carbon steels used in general applications, the SAE-1010 and SAE-1045, and an 304 austenitic stainless steel. The ARB process simulation was carried out at a 500°C, using a total equivalent strain of 4.0, with increment of 0.8 per pass and constant strain rate of 10-1s-1. Were also analyzed the effect of deformation temperature on grainrefining, for this purpose tests were carried out at 550, 600, 650 and 700°C. The torsion tests are shown to be effective in the ARB process simulation in the three studied steels. After processing a minimum average grain size less than 400nm was achieved for steel with higher carbon content. Significant increase in hardness was also observed, which may be in part attributed to the work hardening and in most part tograin refinement. There is evidence that carbon steels studied here can provide satisfactory ductility in tensile tests and in practical applications. The grain refinement in the three studied steels is due to continuous dynamic recrystallization, assisted in parts by dynamic recovery. The increasing in carbon concentration demonstrates a beneficial effect on the grain refinement, steel with the highest concentration had a mlower average grain size and higher hardness. Fragmented cementite particles are formed during deformation and act increasing the density of geometrically necessary dislocations and reducing the mobility of recrystallized grains. The average grain size of steels decreased continuously with the increse in deformation temperature, thisreduction was less pronounced in the SAE-1045 steel. A higher concentration of cementite particles also seems to contribute to greater stability of the grains at higher processing temperatures. There is a critical strain at which occurs grain refinement, this deformation is smaller in the steel with higher carbon concentration. There is also astrain from which grain refinement was stopped, saturation strain, where the average grain size reached a steady state value, there is no more grain refinement. It also occurs saturations of mechanical properties when a certain strain is reached. The experimental data are reasonably modeled by the Kocks-Mecking model. The warm torsion tests prove to be a effective tool in simulating the ARB process, also proved tobe a promising new tool in the study of ultra-fine grained metals by means of severe plastic deformation. The severe torsion can be applied to the study of other metals and alloys that havedifficulty to be processed in mill laboratories: it provide a better temperature control, better control of speed deformation, precision interpass time control and is a testingrelatively accessible.